Development of massive open online course (MOOC) based on addie model for catering courses - Mohd Erfy Ismail; Pipit Utami; Irwan Mahazir Ismail; Norhasyimah Hamzah; Hairuddin Harun (ADGVI & Graduate School of Universitas Negeri Yogyakarta, 2018)
Nowadays, innovation for teaching aids is an important requirement to ensure the teaching and learning process can run smoothly. Coinciding with the Malaysia Education Blueprint 2013-2025 (Ministry of Education) through the ninth surge of Global Online Learning, the development of the Massive Open Online Course (MOOC) was built. The ADDIE model has been adapted for this development. The study aims to develop an appropriate interactive learning for Food and Beverage Presentation subjects based on the Vocational College (VC) syllabus. In research development, researchers use Richey and Klein research recommendations, using Alpha and Beta tests in the evaluation phase of the study. The population of the study involved 155 Catering students at Muar Vocational College and the sample of the study were 60 of third and fourth-year Diploma students. The sampling method used is the purposive sampling and the instrument used in the form of the questionnaire. Data collected were collected and analyzed descriptively using Statistical Packages for Social Science (SPSS) version 23.0. Based on the analysis, the reliability value of the instrument is 0.997 and shows that the reliability of the instrument is at a high level. The findings show that the use of MOOC can increase computer literacy (3.75), interest (3.78) and student learning styles (3.75) and make the learning process more interesting. In addition, the findings show that the use of the MOOC application can help students in improving the performance and achievement of students in learning and thus can be an alternative to diversifying the teaching and learning process in VC.